Pengaruh Lingkungan Kerja Dan Komitmen Organisasi Terhadap Kepuasan Kerja Perawat (Studi pada RSU PKU Muhammadiyah Tunas Medika Purworejo) - Baraba, Ridwan (Jurnal Bisnis Teori & Implementasi)
This research aims to find out : 1). The effect of work enviroment on job satisfaction, 2). The effect of organizational commitment on job satisfaction, 3)Â The dominant variabel which influence the job satisfaction, whether it is work enviroment or organizational commitment. Data were collected from 60 respondents by means ofÂ population method. Data analysis was counducted through descriptive analysis, which include the research instrument validity test by using product moment correlation and reliability testing by using Cronbachâs Alpha technique, hpypotesis testing which multiple linear regression analysis with the t test and coefficient of determination. The result of the research showed that: 1). Work enviroment have a positive and significant impact on job satisfaction, 2). Organizational commitment have a positive and significant impact on job satisfaction, 3) Organizational commitment variabels have more dominant influence on job satisfaction than work enviroment.Â